Islay Jazz Festival - Medbøe, Haftor; Maclean, Diane (Jazz Research Journal, 2020)
This article considers the ecologies and stakeholder interests that overlap in the staging of an annual jazz festival on a small Scottish island in the Outer Hebrides. Through interviews with festival promoters, performers and audience members, alongside insights from island residents, we interrogate the special circumstances governing the presentation of a festival of ostensibly urban music in a rural island location. Constructions of identity and myth are observed to permeate narratives around both festival and island, often symbiotically intertwined to mutual benefit. Nonetheless, tensions between incomer and visitor, the rural and the urban, ‘high’ and ‘low’ arts, nostalgia and progress are seen to emerge. In the discussion of the complexities involved in the import of a jazz festival to an island steeped in its own history, and internationally recognized for its manufacture and export of distinctive Scotch whisky, this article seeks to explore universal themes of identity construction through a finite study of a distinctly situated cultural festival.